Absence of neurotoxicity and hypernociception in rats administered the antiretroviral drug stavudine - Makweya, Sibongile (My University, 2013)
Stavudine (d4T), a nucleoside reverse transcriptase inhibitor (NRTI) used to treat infection by the human immunodeficiency virus (HIV), is associated with the development of peripheral neuropathy and pain in HIV-positive patients. The mechanisms of this toxic neuropathy are poorly understood, primarily due to a lack of relevant animal models of the neuropathological process initiated by d4T. I investigated whether daily oral or subcutaneous administration of d4T produces neuropathological changes. Compared to previous descriptions of mechanical hypersensitivity induced by daily oral administration of d4T to rats at a dose of 50 mg.kg-1over a four week period, I found that this dosing regimen did not result in hyperalgesia to blunt and punctuate mechanical stimuli applied to the gastrocnemeus muscle. In agreement with the lack of hyperalgesia, oral administration of d4T at 50 mg.kg-1 over a four week period did not induce significant myelinated nerve fibre loss or morphological changes in the sciatic nerve. I then investigated whether administering 100 mg.kg-1 d4T subcutaneously, and therefore avoiding first-pass metabolism, to rats for four weeks causes hyperalgesia and neuropathological changes in nerve morphology. Daily subcutaneous injections of d4T at 100 mg.kg-1 over a four week period did not induce the development of hyperalgesia to a punctate mechanical stimulus applied to the tail or significant neuropathology. My studies demonstrate that multiple administrations of d4T at 50 mg.kg-1 orally or 100 mg.kg-1 subcutaneously over a four week period do not induce hyperalgesia or nerve fibre pathology in rats. Thus, developing a robust animal model of d4T-induced neuropathy may be challenging in the absence of HIV-infection, such that occurs in infected patients. Key words: HIV, ART, d4T, hypernociception
Keywords: HIV; ART; d4T; hypernociception